Numerical Simulation of Fluid Flow on An Open Channel with Parabolic Cross-section - Erianto, Elvi Syukrina; Aprilia, Nadya Zulfani; Khumaeroh, Mia Siti (ISTEK, 2025)
Water is a vital resource whose movement is influenced by various factors such as gravity and frictional force. The cross-sectional shape of a channel can significantly influence the friction force,consequently, affect the flow characteristics. One of the interesting cross-sectional shapes to analyze is parabolic because of its unique geometric properties. This study aims to conduct a numerical simulation of open channel flow within a parabolic cross-section using a modified Shallow Water Equation and the Finite Volume Method implemented with a staggered grid scheme. The mathematical model used takes into account the influence of the parabolic shape through the calculation of Manning's friction, which depends on the hydraulic radius. The Shallow Water Equations, consisting of the continuity and momentum equations, are solved numerically through spatial and temporal discretization. The simulations are perfomed using Scilab to generate visualizations of the water depth and flow velocity distribution under various geometric conditions. This study produces simulations of one-dimensional (1D) and two-dimensional (2D) dam-break flows with a parabolic cross section and compares them with the rectangular cross-section. The simulation results show that the finite volume method with the staggered grid scheme provides stable solutions and is capable of accurately describing the flow behavior across different channel geometries.